Human pancreatic islet transplantation: an update and description of the establishment of a pancreatic islet isolation laboratory - Rheinheimer,Jakeline (2015)
Type 1 diabetes mellitus (T1DM) is associated with chronic complications that lead to high morbidity and mortality rates in young adults of productive age. Intensive insulin therapy has been able to reduce the likelihood of the development of chronic diabetes complications. However, this treatment is still associated with an increased incidence of hypoglycemia. In patients with “brittle T1DM”, who have severe hypoglycemia without adrenergic symptoms (hypoglycemia unawareness), islet transplantation may be a therapeutic option to restore both insulin secretion and hypoglycemic perception. The Edmonton group demonstrated that most patients who received islet infusions from more than one donor and were treated with steroid-free immunosuppressive drugs displayed a considerable decline in the initial insulin independence rates at eight years following the transplantation, but showed permanent C-peptide secretion, which facilitated glycemic control and protected patients against hypoglycemic episodes. Recently, data published by the Collaborative Islet Transplant Registry (CITR) has revealed that approximately 50% of the patients who undergo islet transplantation are insulin independent after a 3-year follow-up. Therefore, islet transplantation is able to successfully decrease plasma glucose and HbA1c levels, the occurrence of severe hypoglycemia, and improve patient quality of life. The goal of this paper was to review the human islet isolation and transplantation processes, and to describe the establishment of a human islet isolation laboratory at the Endocrine Division of the Hospital de Clínicas de Porto Alegre – Rio Grande do Sul, Brazil.